Verification of Unstructured Workflows Via Propositional Logic - LIANG, Qianhui (Althea) (Institutional Knowledge at Singapore Management University, 2008)
The concept of unstructured workflows is useful for both research and practical purposes. While sometimes it is preferable to transform unstructured workflows into structured ones, unstructured workflows may be more meaningful to business people. Furthermore, transformation from unstructured to structured workflows may be troublesome at times. As such, it is important to be able to verify unstructured workflows directly. In this paper, we take a different perspective by focusing on the verification of unstructured workflows using a propositional-logic-based approach. We demonstrate that logic-based verification can derive similar results between an unstructured workflow and its corresponding structured workflow. We further develop a conceptual framework that characterizes the propositional logic approach to verification of unstructured workflows.